PSYCHOLOGICAL AND PEDAGOGICAL BASES OF FORMATION OF THE FUTURE SPECIALISTS' INDIVIDUAL STYLE OF PROFESSIONAL ACTIVITIES - Lavrentieva Olena; Krupskyi Oleksandr (Alfred Nobel University Publisher, 2022)
The article studies the problem of the future specialist's professional formation as a subject of professional activity, which is characterized by originality and peculiarity in the realization of labour functions. The aim of the article is to reveal the essence and content of the individual style of professional activity, its structure and formation mechanisms; determination of pedagogical terms that contribute to the shaping of the optimal individual style of future specialists' professional activity during their professional preparation process. A complex of research methods has been used, namely: content analysis, generalization and specification in the provisions of the theory of activity and professional pedagogy regarding the essence of the individual style of activity, modelling of the structure of the individual style of professional activity, substantiating the pedagogical terms of its formation in future specialists during their professional preparation process. It has been established that the individual style of professional activity is a complex personal creation including a stable system of work methods and techniques, and determining a certain behaviour strategy in their labour activity. It has been shown that the structure of an individual style can be presented in the form of a content core and an extension to it; it is formed as a result of the action of mechanisms of adaptation, compensation and correction during the subject's mastery of professional activity. It has been found that the individual style of professional activity can be characterized by means of the peculiarity of the ratio of the indicative, executive and control types of professional activity in its structure. It can be defined by way of procedural, personal originality, and productivity parameters, as well as one's having the developmental, corrective and adaptive potential, and motivation in detecting and shaping the style. It has been emphasised that the style of professional activity, at the same time, is both a factor and a consequence of the person's individual professional development. During the gaining professional experience process, the innate properties of the nervous system, and acquired intellectual, emotional, and behavioural qualities are integrated and a person's distinctive features and individual abilities are formed ensuring their efficiency and productivity in achieving the results. It has been highlighted that such leading methodological approaches as systemic, personal-activity, axiological and acmeological ones are effective means to shape the future specialists' individual style of professional activity. They make it possible to form not individual features or characteristics, but an integral dynamic psychological system of individual active adaptation to the conditions of the professional environment via involvement in the study and professional activities, taking into account personality traits and value attitudes and focusing on achieving the top of the professional mastery. Pedagogical terms for the formation of the future specialists' individual style of professional activity have been identified and substantiated. They include taking into account the individual and psychological characteristics of future specialists, introducing means of complex differentiation to develop adequate self-assessment and attitudes in the performance of labour actions, purposeful formation of a system of rational labour methods, as well as creation of a positive microclimate and an atmosphere of co-creation and cooperation in classes, which will ensure the consolidation of original methods of carrying out professional activities.